2015
DOI: 10.3758/s13423-015-0865-9
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluating the effectiveness of n-back training on transfer through the Bayesian lens: Support for the null

Abstract: A recent meta-analysis by Au et al. Psychonomic Bulletin & Review, 22, 366-377, (2015) reviewed the n-back training paradigm for working memory (WM) and evaluated whether (when aggregating across existing studies) there was evidence that gains obtained for training tasks transferred to gains in fluid intelligence (Gf). Their results revealed an overall effect size of g = 0.24 for the effect of n-back training on Gf. We reexamine the data through a Bayesian lens, to evaluate the relative strength of the eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
85
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 45 publications
6
85
0
Order By: Relevance
“…These findings support the concerns of many researchers (24,27,(29)(30)(31)(32), who suggest that placebo effects may underlie positive outcomes seen in the cognitive-training literature. By capitalizing on the self-selecting tendencies of participants with strong positive beliefs about the malleability of intelligence, we were able to induce an improvement in Gf after 1 h of working memory training.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These findings support the concerns of many researchers (24,27,(29)(30)(31)(32), who suggest that placebo effects may underlie positive outcomes seen in the cognitive-training literature. By capitalizing on the self-selecting tendencies of participants with strong positive beliefs about the malleability of intelligence, we were able to induce an improvement in Gf after 1 h of working memory training.…”
Section: Discussionsupporting
confidence: 79%
“…ref. 27). However, researchers have yet to identify, test, and confirm a clear mechanism underlying fluid intelligence gains after cognitive training (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have observed that training executive functions can influence conceptually-related cognitive outcomes such as fluid intelligence (e.g., Jaeggi, Buschkuehl, Jonides, & Perrig, 2008), these studies often share similar limitations to those examining the effects of self-control training (e.g., a lack of active control conditions; Shipstead, Redick, & Engle, 2010). Studies comparing executive function training with active control conditions have tended to find that training leads to improvements only on tasks that are very similar to the trained task, with no evidence for generalization beyond those tasks to other cognitive abilities (e.g., Dougherty, Hamovitz, & Tidwell, 2015;Harrison et al, 2013;Redick et al, 2013). In the few studies that have assessed the effects of executive function training on self-control outcomes, there is also a lack of consistent evidence for transfer.…”
Section: Integrating the Present Findings With Previous Researchmentioning
confidence: 99%
“…Although the idea of improving general cognitive functioning within a few weeks is enticing, there is also accumulating evidence against a generalized effect of WM training (e.g., Clark et al 2017;De Simoni and von Bastian 2017;Guye and von Bastian 2017;Sprenger et al 2013). Even on the meta-analytic level, evidence is mixed regarding the effectiveness of cognitive training in both younger and older adults (e.g., Au et al 2015;Dougherty et al 2016;Karbach and Verhaeghen 2014;Kelly et al 2014;Lampit et al 2014;Melby-Lervåg and Hulme 2013;Melby-Lervåg et al 2016;Schwaighofer et al 2015;Soveri et al 2017). Aside from design and methodological choices potentially explaining the diverging findings (e.g., Noack et al 2009;Shipstead et al 2012), many authors increasingly articulated the potentially important influence of individual differences on cognitive training trajectories and outcomes (e.g., Buitenweg et al 2012;Guye et al 2016;Könen and Karbach 2015;Shah et al 2012;von Bastian and Oberauer 2014 Individual differences in cognitive functioning (e.g., Ackerman and Lohman 2006) and learning potential (e.g., Stern 2017) accentuate with increasing age (e.g., Rabbitt et al 2004) and have been shown to be related to personality (e.g., Graham and Lachman 2012), cognition-related beliefs such as need for cognition (NFC; e.g., Fleischhauer et al 2010;Hill et al 2013), and everyday life activities (e.g., Jopp and Hertzog 2007).…”
mentioning
confidence: 99%